A numerical study of bodies in low reynolds number and their comparison in moving and stationary frames - Maitreya Mukherjee (Nanyang Technological University, 2020)
The thesis aims to compare the results of numerical simulation of fluid dynamics in moving and stationary frames. Three flow configurations were tested, namely a flat plate, a NACA0009 aerofoil and a cylinder, essentially changing from thin to bluff body types. The flow domain and the body mesh are meshed separately and combined using the overset technique. In the stationary frame, the body mesh is held stationary while the flow is moving. Conversely, in the moving frame the body moves in a quiescent flow. All cases were performed at Reynolds number of 400. The results for each of the three different stationary cases were compared with their respective moving cases. The results for the flat plate and aerofoil for both the moving and stationary frames were in reasonable agreement. The discrepancy arose for the cylinder, where the drag for the stationary case was approximately twice of that of the moving case. Further analysis indicates that pressure drag is the dominant factor of the discrepancy, suggesting that the fluid dynamics of bluff bodies in moving frame may not be accurately transferred into the stationary frame. This is contrary to what is expected from the the invariant nature of the Navier-Stokes equation.